Physical Activity, Arterial Stiffness, and Risk of Cardiovascular Disease and Death in Men and Women : A Population-Based Study - Holm, Johannes; Lippe, Viktor Eriksson; Nilsson, Peter M.; Wadström, Benjamin Nilsson (Angiology, 2025)
Physical activity lowers risk of cardiovascular disease and may also decrease arterial stiffness. We aimed to investigate whether arterial stiffness can explain part of the association between physical activity and the risk of major adverse cardiovascular events (MACE) and all-cause death in men and women. We followed 2583 individuals from the Malmö Diet and Cancer study (2007-2012) for occurrence of MACE in Swedish nationwide registries (mean follow-up: 9 years). Physical activity was self-assessed using a questionnaire. Arterial stiffness was assessed by carotid-femoral pulse wave velocity (cfPWV), the gold standard. Survival analyses were performed using Cox regression. In all individuals, multivariable adjusted hazard ratios per 1 m/s higher PWV were 1.09 (95% confidence interval: 1.05-1.14) for MACE and 1.06 (1.03-1.09) for death. Explained risk estimates for the association from physical activity through arterial stiffness were 12% (0%-100%) for risk of MACE and 5% (1%-16%) for risk of death; in men, corresponding results were 7% (0.4%-28%) and 7% (0%-51%). For women, physical activity was not associated with risk of MACE or death. In conclusion, arterial stiffness may explain part of the association from physical activity to risk of death and potentially risk of MACE in men.
Keywords: arterial stiffness; cardiovascular disease; mortality; physical activity; sex